High Signal Intensity on Diffusion-Weighted Images Reflects Acute Phase of Deep Vein Thrombus - Gi, Toshihiro; Kuroiwa, Yasuyoshi; Yamashita, Atsushi; Mizutani, Yuko; Asanuma, Taketoshi; Miyati, Tosiaki; Maekawa, Kazunari; Aman, Murasaki; Imamura, Takuroh; Asada, Yujiro (Thrombosis and Haemostasis, 2020)
The effects of antithrombotic therapy on deep vein thrombosis (DVT) can be affected by thrombus age, which cannot be reliably determined by noninvasive imaging modalities. We investigated whether magnetic resonance (MR) diffusion-weighted imaging (DWI) can localize and determine the age of venous thrombus in patients with DVT, animal models, and human blood in vitro. Signal intensity (SI) on DWI and the apparent diffusion coefficient (ADC) of thrombi were assessed in eight patients with DVT using a 1.5-T MR imaging (MRI) system. We assessed the organizing processes as venous thrombus developed in the rabbit jugular vein using a 3.0-T MRI system over time. We also assessed MRI signals of human blood in vitro using the 1.5-T MRI system. Venous thrombi were detected by DWI as areas of high or mixed high and iso SI in all patients. The ADCs were lower in the proximal, than in the distal portion of the thrombi. The thrombi of rabbit jugular veins histologically organized in a time-dependent manner, with high SI on DWI at 4 hours, mixed high and iso SI at 1 and 2 weeks, and iso SI at 3 weeks. The ADC correlated negatively with erythrocyte content, and positively with smooth muscle cells, macrophages, hemosiderin, and collagen content. MRI signals of human blood in vitro showed that ADCs were affected by erythrocyte content, but not by blood clotting. MR-DWI can detect venous thrombus, and high SI on DWI accompanied by a low ADC might reflect erythrocyte-rich, acute-phase thrombi.
Keywords: deep vein thrombosis; diffusion-weighted imaging; erythrocyte; magnetic resonance imaging; pathology